A Rare Presentation of Intestinal Tuberculosis with Transverse Colon Perforation in an Infant - Shivprasad Mundada; Nehal B Shah; Vikas Solunke; Kiran B Bhaisare (Pediatric Infectious Disease)
To report a case of a 1-year-old female with intestinal tuberculosis (TB) causing transverse colon perforation and peritonitis.